AKTIVITAS ANTIBAKTERI KURKUMIN DAN KOMPLEKS TEMBAGA (II) KURKUMIN TERHADAP S.AUREUS DAN E.COLI - Firdaus, Giska Ristianty; Silalahi, Imelda Hotmarisi; Ardiningsih, Puji (Indonesian Journal of Pure and Applied Chemistry, 2024)
Copper (II) complex of curcumin was prepared from the reaction between curcumin and a metal precursor (CuCl2.2H2O) in ethanol with a mole ratio curcumin to metal 2:1. The FTIR spectrum of Cu2+-curcumin shows a change in the absorption band and a shift in the wave number, especially in the absorption band of the phenolic "“OH group 3510.45 cm-1 which is a stretching vibration that becomes wider and shifts to a larger wave number, namely 3514.30 cm-1. Compared with free curcumin spectrum the absorption band of the C=O functional group shows a change where in free curcumin is at 1627.92 cm-1 while in the Cu2+-curcumin complex the is at 1735.93 cm-1 this indicate the coordination of metal ions with curcumin. The IR spectrum shows a typical absorption band for the metal oxygen group, Cu-O 480.28 cm-1 in the Cu2+-curcumin complex. The UV-Vis spectrum of the Cu2+-curcumin complex show a shift towards a larger wavelength (red shift/batochromic) of (~2 nm). Antibacterial activity of Cu2+-curcumin complex compound is active in inhibiting S.aureus and E.coli. After complexation, the activity against the tested microorganisms generally increased and the complex showed higher activity than free curcumin.